Penegakan HAM dalam perspektif hukum dan keadilan sosial - Ulum, Miftahul Miftahul; Ulum, Miftahul Miftahul (Maliki Interdisciplinary Journal, 2026)
Human Rights (HAM) are fundamental rights that every person possesses from birth and must be protected and upheld by the state. The enforcement of human rights is very important to ensure that social justice can be experienced by all members of society. This study aims to examine the enforcement of human rights from a legal perspective and its relationship with social justice in Indonesia.This research uses a normative legal method, which involves analyzing various laws and regulations as well as academic literature. The results show that the enforcement of human rights in Indonesia still faces many challenges, such as weak law enforcement, low public awareness of human rights, and ongoing social inequality.Therefore, improvements in the legal system are needed, along with strengthening institutions that handle human rights and encouraging active public participation so that social justice can truly be achieved for all.